Intrapersonal Communication Model and Self-Concept among Female Drivers as Heads of Household in Medan City - Ariska, Juli; Nurbani, Nurbani; Kurniawati, Dewi (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
As Indonesia’s third-largest city, Medan has witnessed rapid growth in ride-hailing services, providing employment opportunities for women who challenge traditional gender roles by working as motorcycle taxi drivers. In a predominantly patriarchal society, female drivers who also serve as heads of households face unique challenges in balancing professional responsibilities with cultural expectations. This study examines the intrapersonal communication processes and self-concept development of female motorcycle taxi drivers in Medan. Using a qualitative phenomenological approach, data were collected through observations, in-depth interviews, and focus group discussions with five primary informants—women who work as online motorcycle taxi drivers while serving as heads of households. Additional insights were gathered from five triangulation informants, including a Gojek task force member, a psychologist, the drivers’ children, and fellow drivers. The findings indicate that despite experiencing gender discrimination and social stigma, these women construct positive self-concepts through self-talk and cognitive reframing. This study introduces the RISE Communication Model (Resilience, Insight, Self-Empowerment, Evolution), demonstrating how these women develop resilience while maintaining their cultural identity. The model provides a conceptual framework for understanding psychological adaptation mechanisms among women in non-traditional occupations within Medan’s diverse urban landscape.